End-user empowered sales information system for URC-AIG hogs division through the application of business intelligence (BI) tools - Inventado, Carlito R. Jr (University of the Philippines Diliman, 2009)
The project covers the evaluation of the current sales information system and customer needs. It also involves the application of BI tools for the extraction of URC-AIG's sales data from the existing ERP system into a data warehouse and its formulation into different AIG sales cubes. Using a front end application (BARS), end-users can generate valuable information from sales data for their analysis and reporting purposes.